2023
DOI: 10.1227/neu.0000000000002668
|View full text |Cite
|
Sign up to set email alerts
|

The Limited Utility of the Hospital Frailty Risk Score as a Frailty Assessment Tool in Neurosurgery: A Systematic Review

Michael M. Covell,
Joanna Mary Roy,
Kavelin Rumalla
et al.

Abstract: BACKGROUND AND OBJECTIVES: The Hospital Frailty Risk Score (HFRS) is an International Classification of Disease 10th Revision-based scale that was originally designed for, and validated in, the assessment of patients 75 years or older presenting in an acute care setting. This study highlights central tenets inherent to the concept of frailty; questions the logic behind, and utility of, HFRS' recent implementation in the neurosurgical literature; and discusses why there is no useful role for HFRS as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…4,5 The paper titled "The Limited Utility of the Hospital Frailty Risk Score as a Frailty Assessment Tool in Neurosurgery: A Systematic Review" presents a critical analysis of the Hospital Frailty Risk Score (HFRS) and its application in neurosurgical contexts. 6 The authors of this paper conducted a comprehensive review of 17 papers, in accordance with PRISMA criteria. They found that these studies had a consensus in reporting that HFRS was predictive of postoperative mortality, complications, extended length of stay, and discharge to a higher level of care facility (skilled nursing facility).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…4,5 The paper titled "The Limited Utility of the Hospital Frailty Risk Score as a Frailty Assessment Tool in Neurosurgery: A Systematic Review" presents a critical analysis of the Hospital Frailty Risk Score (HFRS) and its application in neurosurgical contexts. 6 The authors of this paper conducted a comprehensive review of 17 papers, in accordance with PRISMA criteria. They found that these studies had a consensus in reporting that HFRS was predictive of postoperative mortality, complications, extended length of stay, and discharge to a higher level of care facility (skilled nursing facility).…”
mentioning
confidence: 99%
“…4 HFRS is criticized for being computationally impossible to distinguish whether frailty assessment occurs preoperatively or postoperatively, which is essential for neurosurgical frailty research. 5,6,11 Hence, the application of the tool in neurosurgical population introduces inaccuracies in the measured "frailty" of the surgical population and hence does not have practical utility in the context of guiding personalized intervention decisions or generating treatment guidelines without further validation studies. However, this does not entirely discredit previous studies using HFRS to predict mortality; rather, it might be possible to reframe their interpretation.…”
mentioning
confidence: 99%
See 3 more Smart Citations